PENTINGNYA KEMAMPUAN MANAJERIAL DA’I TERHADAP KEBERHASILAN LEMBAGA DAKWAH - Bella Zenita (Mudabbir: Jurnal Manajemen Dakwah, 2022)
This study describes the managerial skills that must be possessed at every level of management, so not only at the top level. The goal is to understand and know the importance of the managerial ability of a da'i or preacher in a da'wah institution. This study uses a qualitative descriptive method with the type of literature which means collecting from various existing scientific works such as journal articles, books, theses and theses related to the theme. The results of this study are to mention the importance of the da'i's managerial ability to the success of da'wah institutions, including being able to manage da'wah institutions well because they have mastered technical skills, human skills, and conceptual skills, being able to be one of the causes of the success of da'wah institutions, being able to implement and develop mindset in sharia management, able to strengthen harmonious relations between members, move members to work better, motivate members to learn managerial skills, have a positive impact on da'wah institutions such as good reputations, and can excel da'wah institutions, and be able to introduce them in a creative way , innovative, attract the attention and interest of the surrounding community and even the wider community.